Implementasi Model Creativity Authentic Literacy Learning (CALL) untuk Meningkatkan Aktivitas Belajar Calon Guru MI - Putra, Miftakhul Ilmi S.; Anwar, M. Ansor; Mundilarto, Mundilarto; Widodo, Wahono; Jatmiko, Budi (Universitas Pesantren Tinggi Darul 'Ulum, 2019)
This study was aimed to investigate the influence of Creativity Authentic Literacy Learning Model with development to increase student activity in PGMI. Students of 5th semester majoring in PGMI, Unipdu, Jombang, were subjected with the tested learning method. The study was conducted in September-November 2018 with experimental method. Students’ performance was assesed through cognitive tests, observation, and interviews. Results of this study indicate that Science learning with Creativity Authentic Literacy Learning skill of learning to improve students achievement. Overall Creativity Authentic Literacy Learning syntax implemented 100%. Student activity during learning activities show that students learn actively.